Signal-friendly metal surface
By introducing frequency-selective surfaces and simplifying the structure in low-emissivity coatings, the problems of attenuation of telecommunication frequency signals and insufficient durability of existing coatings are solved, resulting in coated products with high transparency, low radiation, and signal-friendly properties, suitable for architectural and automotive glass.
Patent Information
- Application Number
- CN202380057285.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2025-10-28
AI Technical Summary
Existing low-emissivity coatings reflect IR radiation and transmit visible light, but they also significantly attenuate telecommunication frequency signals, especially 5G signals. Furthermore, their durability and weather resistance are insufficient, leading to signal shielding and durability issues in building and automotive applications.
The frequency selective surface (FSS) design reduces the attenuation of telecommunication frequency signals by etching periodic or non-periodic patterns on a metal layer, and combines a simplified low-emissivity coating structure, including a metal IR reflective layer, a dielectric layer, and a protective layer, to prepare coated articles using laser etching or photolithography.
It effectively reduces the attenuation of telecommunication frequency signals, improves the durability and weather resistance of coated products, and makes them suitable for building and automotive windows while maintaining high transmittance and reflectance, reducing the shielding effect on signals.
Smart Images

Figure CN120858196A_ABST
Abstract
Description
Priority document
[0001] This application claims priority to Australian Provisional Patent Application No. 2022901475, filed on May 31, 2022, entitled “Coated Articles with Low-Emissivity Coating and / or Hard Coating,” the entire contents of which are hereby incorporated by reference. Technical Field
[0002] This disclosure generally relates to coated articles and methods for preparing the same. In a particular form, this disclosure relates to coated articles comprising a metal layer and having signal-friendly telecommunications frequency transmission, and methods for preparing the same. Background Technology
[0003] Low-emissivity (low-E) coatings consist of a series of very thin films that reflect solar infrared radiation while allowing some visible light to pass through. Low-emissivity coatings are used in architectural glass, automotive windows, and solar collectors due to their excellent energy-saving performance. For example, the ability of low-emissivity products (such as windows) to reflect solar infrared radiation can significantly reduce indoor building temperatures in summer and retain indoor heat in winter, thereby minimizing the use of air conditioning and heating systems, respectively. Additionally, their high transmittance in the visible light range greatly helps reduce the need for artificial lighting during the day.
[0004] To achieve this combination of reflectivity and transmittance, low-emissivity coatings typically consist of a conductive metal layer and a dielectric layer. In some cases, a multilayer system of dielectric-silver-dielectric material is used, where a thin silver layer (approximately 10 nm) reflects long-wavelength IR, and the dielectric layer both protects the silver and provides anti-reflective properties. Common examples of dielectric materials include TiO2, SnO2, or ZnO, and they are typically deposited via magnetron sputtering.
[0005] For architectural windows, the most commonly used coating is a low-emissivity (LEC) coating. While LECs do reflect heat and are highly transparent due to their metallic content, they are made with a rather complex structure, typically involving more than 20 layers and 10 different materials, making the manufacturing process expensive. Additionally, commercial LECs have durability issues due to corrosion of the IR reflective layer, which is usually made of silver (Ag), so they are typically placed within a cavity between double-glazed windows to prevent weathering.
[0006] Traditionally, in the automotive industry, glass panels with adhesive window films consisting of one or more PET sheets containing carbon, ceramic nanoparticles, or dark dyes have been used to darken car windows to block IR radiation from the sun. However, these films absorb rather than reflect IR radiation. This means that the absorbed radiation is re-radiated into the car through conduction and convection, thus failing to protect the car from high temperatures. Furthermore, to be effective at heat insulation, they exhibit low visible light transmittance, making them unsuitable for public transportation or vehicle windshields.
[0007] Another drawback of existing low-emissivity coatings is that thin metal layers attenuate microwave and radio frequency signals, especially in high-frequency ranges such as 5G wireless signals (600MHz–100GHz). For example, if a car is equipped with metal-based low-emissivity windows, the window will act as a Faraday cage, significantly reflecting or attenuating useful telecommunications signals. With the development of wireless devices, strong and stable signal strength inside buildings is also important. The attenuation of signals as they pass through objects can also be measured by shielding efficiency (SE). Shielding efficiency is defined as the logarithm of the ratio of the magnitude of the incident electric field to the magnitude of the transmitted electric field, and is expressed in decibels (dB). 0dB means no attenuation. For example, in public transportation, the current strategy for amplifying signals is to install repeater devices. However, this type of device only amplifies selected frequencies and needs to be replaced when communication standards change. These devices are both expensive and power-intensive. Another option is to use ultra-wideband antennas, but their performance depends on their installation location on the vehicle body, and the distance between the metal window and the antenna significantly reduces their efficiency. Antennas can also be integrated into heated windows. However, these antennas will only cover the FM / TV range (50-800MHz). The latest integrated window antennas can cover 4G LTE and low-frequency 5G signals; however, these antennas will also need to be replaced when communication standards change.
[0008] Products with low-emissivity coatings (e.g., doors and windows) are often exposed to harsh and extreme conditions in real-world applications, making weather resistance, robustness, and durability crucial.
[0009] There remains a need for coated articles and methods for preparing them that can alleviate or mitigate one or more of the aforementioned problems. In other words, it is desirable for coated articles to have a simplified, low-cost structure while maintaining visible light transmittance and IR radiation reflectance comparable to existing commercial products. Alternatively, it is desirable for coated articles to have lower signal transmission attenuation at telecommunication frequencies. Alternatively, it is desirable for coated articles to have improved durability, abrasion resistance, and weather resistance. Summary of the Invention
[0010] According to a first aspect, a coated article comprising a metal layer is provided, wherein the metal layer has a frequency-selective surface configured to reduce attenuation of telecommunication frequency signal transmission.
[0011] In some embodiments, the metal layer is a metallic IR reflective layer within a low-emissivity coating included in the coated article.
[0012] In some embodiments, the frequency selection surface includes a periodic pattern selected from the group consisting of periodic hexagonal grids, periodic square grids, periodic triangular grids, periodic circular grids, periodic kagome grids, and / or a non-periodic pattern such as penrose tiling.
[0013] In some embodiments, the cell size of the periodic pattern on the frequency-selective surface is less than about 2 mm, for example, less than about 1 mm, and the aperture linewidth is from about 5 μm to about 60 μm, for example, from about 30 μm to about 60 μm. In some further embodiments, the cell size of the periodic pattern on the frequency-selective surface is about 0.5 mm and the aperture linewidth is about 50 μm. In even further embodiments, the frequency-selective surface comprises a periodic hexagonal grid with a cell size of about 0.5 mm and an aperture linewidth of about 50 μm.
[0014] In some embodiments, the telecommunication frequency is used for fifth-generation (5G) communications. In some further embodiments, the attenuation of the telecommunication frequency signal transmission is reduced from about 30 dB to about 1 dB compared to a coated article with a metal layer that does not have a frequency-selective surface.
[0015] In some embodiments, the metal layer includes silver (Ag), gold (Au), copper (Cu), aluminum (Al), zinc (Zn), niobium (Nb), titanium nitride (TiN), Ag / Au alloy, Ag / Cu alloy, Ag / Al alloy, and NbN. x NbCr, NbCrN x and / or NbZrO x Silver (Ag), gold (Au), or copper (Cu) are particularly suitable for metallic IR reflective layers. In some further embodiments, the low-emissivity coating comprises a metallic layer. In even further embodiments, the thickness of the metallic layer is from about 5 nm to about 25 nm, preferably from about 10 nm to about 20 nm.
[0016] In some embodiments, the coated article includes a low-emissivity coating supported by a substrate, and the low-emissivity coating includes, from the substrate outward, a dielectric layer, a protective layer, a metal IR reflective layer as a metal layer, a protective layer, and a dielectric layer.
[0017] In some embodiments, the substrate of the coated article is substantially made of plastic or glass, which may be flexible or rigid. In some specific embodiments, the plastic used for the substrate is selected from the group consisting of polycarbonate, polyethylene, polypropylene, polymethyl methacrylate, polystyrene, polyamide, polyester, polyester carbonate, polyethersulfone, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), ethylene glycol-modified polyethylene terephthalate (PETG), acrylonitrile butadiene styrene (ABS), acrylonitrile styrene acrylate (ASA), polymethyl methacrylate (PMMA), and polyetherimide. In some further embodiments, the glass used for the substrate is selected from the group consisting of borosilicate glass, flat glass, quartz glass, and soda-lime (float) glass. In some embodiments, the coated article has no between-pane space, and the low-emissivity coating is applied to at least a portion of the surface of the substrate that will be exposed to the environment of use. In some further embodiments, the thickness of the substrate of the coated article is from about 0.4 cm to about 0.5 cm.
[0018] According to a second aspect, a method is provided for reducing the attenuation of telecommunication frequency signal transmission in a coated article comprising a metal layer, wherein the method includes generating a frequency selective surface on the metal layer.
[0019] In some embodiments, the metal layer is a metallic IR reflective layer within a low-emissivity coating included in the coated article.
[0020] In some embodiments, the frequency selection surface includes a periodic pattern selected from the group consisting of periodic hexagonal grids, periodic square grids, periodic triangular grids, periodic circular grids, periodic lattice grids, and / or a non-periodic pattern such as Penrose tessellation.
[0021] In some embodiments, the cell size of the periodic pattern on the frequency-selective surface is less than about 2 mm, for example, less than about 1 mm, and the pore linewidth is from about 5 μm to about 60 μm, for example, from about 30 μm to about 60 μm. In some further embodiments, the cell size of the periodic pattern on the frequency-selective surface is about 0.5 mm and the pore linewidth is about 50 μm. In some further embodiments, the periodic pattern is a periodic hexagonal grid, and its cell size is about 0.5 mm and its pore linewidth is about 50 μm.
[0022] In some embodiments, the telecommunication frequency is used for fifth-generation (5G) communications. In some further embodiments, the attenuation of the telecommunication frequency signal transmission is reduced from about 30 dB to about 1 dB compared to a coated article with a metal IR reflective layer that does not have a frequency-selective surface.
[0023] In some embodiments, no more than about 25% of the area of the metal layer is removed to create a frequency-selective surface on the metal layer. In some further embodiments, no more than about 20% of the area of the metal layer is removed to create a frequency-selective surface on the metal layer. In some further embodiments, no more than about 10% of the area of the metal layer is removed to create a frequency-selective surface on the metal layer. In still further embodiments, about 5% to about 10% of the area of the metal layer is removed to create a frequency-selective surface on the metal layer.
[0024] In some embodiments, a frequency-selective surface is created on the metal layer by laser etching or photolithography. In some further embodiments, one or more stacks are laser-etched to create a frequency-selective surface on the metal layer, and the one or more stacks are selected from: a substrate / metal layer stack, a substrate / protective layer / metal layer stack, a substrate / dielectric layer / protective layer / metal layer stack, a substrate / dielectric layer / protective layer / metal layer / protective layer stack, a substrate / metal layer / substrate stack, a substrate / protective layer / metal layer / substrate stack, a substrate / dielectric layer / protective layer / metal layer / substrate stack, and a substrate / dielectric layer / protective layer / metal layer / protective layer / substrate stack. In a further embodiment, for laser etching, a laser beam enters from either side of the aforementioned stacks to create a frequency-selective surface on the metal layer. In a further embodiment, a multiple pane window including a metal layer (e.g., one or more metal layers) is laser-etched to form a frequency-selective surface on the metal layer.
[0025] According to the third aspect, the use of the coated article according to the first aspect or the coated article prepared according to the second aspect in a motor vehicle or building is provided. Attached Figure Description
[0026] Embodiments of the present invention will be discussed with reference to the accompanying drawings, wherein:
[0027] Figure 1 An exemplary embodiment of a coated article according to the present disclosure is shown, the coated article comprising a simple, economical and durable low-emissivity coating supported by a polycarbonate substrate (0.4 cm).
[0028] Figure 2 The layer-by-layer structure of the coated article according to the present disclosure is shown, wherein the substrate / TiO2 / NiCr / Ag / NiCr has been laser-etched into a honeycomb pattern.
[0029] Figure 3The application of a pulsed laser beam is shown to form a frequency-selective surface with different periodic patterns on an Ag layer, where the darker areas show the Ag coating, the brighter areas show the ablation lines, D = diagonal length, and w = linewidth.
[0030] Figure 4 The Bayer test and the steel wool test are shown before and after. Figure 1 A photograph of a coated product.
[0031] Figure 5 shows a) a low-emissivity coating without a hard coating after 24 hours of salt spray testing, and b) a low-emissivity coating with a hard coating after 1000 hours of salt spray testing.
[0032] Figure 6 Photographs of 20 nm Ag laser-etched with a hexagonal pattern (a) and (b) are shown, along with an SEM image of the hexagonal pattern (c). The darkest areas correspond to the laser paths of the ablation.
[0033] Figure 7 The signal transmission in the automotive frequency range of 72 GHz to 82 GHz is shown.
[0034] Figure 8 The transmission and reflection spectra of the fully low-emissivity coatings without and after laser etching are shown.
[0035] Figure 9 The laser beam is shown to enter from either side of a stack of substrate (polycarbonate) / dielectric layer (TiO2) / protective layer (NiCr) / metal layer (Ag) to create a frequency-selective surface on the metal layer.
[0036] Figure 10 A schematic diagram of the photolithography process used to fabricate FSS hexagonal structures on a low-emissivity coating is shown. Detailed Implementation
[0037] The aspects of this disclosure stem from the inventors' research on multifunctional coated articles, which can have a simple structure and are durable, visible and transparent, capable of reflecting heat energy, efficient for 5G communication, and wear-resistant and weather-resistant. These coated articles can be widely used in, for example, motor vehicles and buildings, such as in glass windows, for energy-efficient and efficient signal transmission.
[0038] As used herein, the term "low-E" refers to a surface condition that radiates a low level of radiant heat and has an emissivity value of approximately 0.04 < ε < approximately 0.4. ε indicates that the coated article can reflect at least approximately 60% to approximately 96% of incident ultraviolet and infrared light.
[0039] The term “IR reflection” as used in this article refers to the ability to reflect infrared (IR) radiation, particularly near-IR and mid-IR radiation.
[0040] The term “telecommunications frequency” as used in this article includes, but is not limited to, signals ranging from about 600 MHz to about 100 GHz, particularly those used for 5G communications, which allow for greater bandwidth, higher data rates, lower latency, and increased network capacity.
[0041] The term "frequency selective surface (FSS)" refers to a periodic resonant pattern designed on a coating that selectively allows or blocks the transmission of electromagnetic waves. For this purpose, frequency selective surfaces are specifically used to reduce attenuation of telecommunication frequency signal transmissions.
[0042] The term "cell" used in this article for frequency-selective surfaces refers to the basic shape that forms a periodic pattern.
[0043] As used herein, the terms “oxide,” “nitride,” and “nitrogen oxide” include various stoichiometry and, unless otherwise stated, all possible stoichiometry.
[0044] The symbols “x” or “y” in the chemical formulas of the compounds disclosed in this article indicate the number of atoms of the element under discussion.
[0045] This document discloses a coated article comprising a low-emissivity coating supported by a substrate, wherein the low-emissivity coating includes a metallic IR reflective layer, a dielectric layer, and a protective layer in contact with the metallic IR reflective layer. The composition of the disclosed coated article can be selected to make it transparent, which is desirable in the automotive, transportation, or construction industries.
[0046] For this purpose, the thermal emissivity ε of the coated article, including the low-emissivity coating, can be about 0.04 < ε < about 0.4. Furthermore, the visible light transmittance of the coated article can be > about 60%, preferably > about 70%, more preferably > about 80%, and / or the IR reflectance of the coated article can be > about 60%, preferably > about 70%. The total thickness of the low-emissivity coating can be about 90 nm to about 120 nm, for example, 110 nm. Transmittance (%T) and reflectance (%R) were measured between 380 nm and 3300 nm using a Cary 5000 spectrophotometer (Agilent Technologies). Visible light solar-weighted transmittance (%T) VIS ) and IR solar weighted reflectance (%R) IR Calculate according to equations 1 and 2 respectively. Where I is the solar irradiance and dλ is the wavelength interval of the integral.
[0047] The low-emissivity coatings disclosed herein can be applied directly or indirectly to a variety of substrates, which can be substantially made of plastic or glass. When the coated article is used as a window for a building or vehicle, the substrate is preferably transparent and has the desired optical quality and impact resistance. The substrate can be colored (e.g., green, gray, or blue). The plastic substrate to be used can be rigid or flexible. For example, the low-emissivity coatings disclosed herein can be applied to a flexible plastic substrate for window film. Examples of suitable plastic substrates include, but are not limited to, polycarbonate, polyethylene, polypropylene, polymethyl methacrylate, polystyrene, polyamide, polyester, polyester carbonate, polyethersulfone, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), glycol-modified polyethylene terephthalate (PETG), acrylonitrile butadiene styrene (ABS), acrylonitrile styrene acrylate (ASA), polymethyl methacrylate (PMMA), and polyetherimide. Examples of glass substrates include, but are not limited to, borosilicate glass, flat glass, quartz glass, and soda-lime (float) glass. Although rigid glass substrates are known, glass substrates can also be flexible, for example, those from Corning Incorporated in Corning, USA. Glass. Polycarbonate is a very strong plastic, naturally transparent, and may be the preferred alternative to glass. A suitable example is Moldlon, commercially available from the Covestro Group. AR polycarbonate. The thickness of the substrate used varies, and the thickness can be from about 0.4cm to 0.5cm.
[0048] It should be understood that the low-emissivity coating can be applied to one or both sides of the substrate. In some embodiments, for double-glazed windows, the low-emissivity coating is applied to the inner sides of each glass pane. The coated articles disclosed herein, comprising a low-emissivity coating and a hard coating, advantageously possess high abrasion and corrosion resistance, which in turn allows the low-emissivity coating to be applied to at least a portion of the surface of the substrate that will be exposed to the environment of use, and eliminates the need to place it between the window panes. In other words, the coated article can exist without interpanel space. The low-emissivity coating reduces solar heat passing through the coated article (e.g., the window) to keep the interior cool without impairing the amount of transmitted visible light. In winter, when internal heat attempts to escape to the cooler exterior, the low-emissivity coating reflects heat back into the interior, thereby reducing radiative heat loss through the coated article. Methods known in the art can be used to coat one or more layers of low-emissivity coating onto a substrate. Examples of these methods are physical vapor deposition (PVD), which includes, but is not limited to, magnetron sputtering, electron beam evaporation, and thermal evaporation.
[0049] The low-emissivity coating comprises one or more metallic IR reflective layers. Typically, the metallic IR reflective layer can comprise or be composed of any reflective metal, such as silver (Ag), aluminum (Al), copper (Cu), zinc (Zn), niobium (Nb), titanium nitride (TiN), Ag / Au alloy, Ag / Cu alloy, Ag / Al alloy, NbN... x NbCr, NbCrN x 、NbZrO x And / or gold (Au). Preferably, silver (Ag) is used for the metallic IR reflective layer due to its relatively neutral color. The thickness of the metallic IR reflective layer can be selected to achieve the desired reflectivity for IR radiation and visible light transmittance. On the one hand, it is desirable for the reflective layer to be thin enough to allow visible light to pass through, thus providing good transmittance. On the other hand, the emissivity of a metallic IR reflective layer (such as an Ag layer) tends to decrease as the sheet resistance decreases. Therefore, to obtain low emissivity, the sheet resistance of the IR reflective layer (such as an Ag layer) should be as low as possible, which means that the thickness should be as thick as possible. A thicker IR reflective layer can be beneficial for thermal performance, but it leads to higher cost and longer manufacturing time for the metallic IR reflective layer. In use, the thickness of the IR reflective layer can be from about 5 nm to about 25 nm, more preferably from about 10 nm to about 20 nm. If desired, two or three metallic IR reflective layers can be used. These low-emissivity coatings are referred to as double-reflective or triple-reflective low-emissivity coatings. The more reflective layers (e.g., Ag layers), the higher the visible light transmittance and IR reflectivity.
[0050] Metallic IR reflective layers can be coated using methods known in the art, including but not limited to magnetron sputtering deposition and pyrolysis. In some embodiments, the IR reflective layer can be sputtered (e.g., at about 3000W) from the cathode of the desired metal onto a protective layer or dielectric layer on a substrate in an inert atmosphere. IR reflective layers fabricated by magnetron sputtering deposition generally perform better than those fabricated by pyrolysis in terms of solar energy control and reducing heat transfer through windows.
[0051] Various protective layers can be coated onto the metal IR reflective layers to provide immediate protection. For example, when a dielectric layer is sputtered on top, it can prevent plasma attack or prevent damage from substances such as O2, O, H2O, and Na. + The diffusion of corrosive substances is prevented. Good adhesion between the protective layer and the metallic IR reflective layer is also desired, as is satisfactory visible light transmittance of the protective layer. Metals, alloys, silicides, nitrides, or any other suitable material to achieve the desired effect can be used. For example, the protective layer can include or be composed of, without limitation, the following materials: nickel-chromium alloy (NiCr), NiCrO... x NiCrN x NiCrOx N y Ni x Ti y O z Ni, Cr, CrN x NiO x Ti, TiO x NbO x ZnO, Al2O3, ZnAlO x Or any combination thereof. Nickel-chromium alloys (NiCr) include, but are not limited to, NiCr (80 / 20 wt%), NiCr (70 / 30 wt%), NiCr (60 / 40 wt%), and NiCr (50 / 50 wt%). In some cases, the protective layer may also be used as an adhesive layer and / or a nucleation layer. For all embodiments herein, the thickness of each protective layer may range from about 1 nm to about 5 nm, preferably from about 1 nm to about 3 nm or from about 2 nm to about 3 nm. A thicker protective layer can contribute to improved durability. If the protective layer is too thin, it is likely to be discontinuous and unable to cover the metallic IR reflective layer, and therefore will not effectively provide sufficient protection. In some embodiments, it is preferred to have a protective layer on each side of the IR reflective layer. However, it is also possible to have a protective layer only on one side of the IR reflective layer. In a preferred embodiment, the protective layer comprises NiCr. More preferably, a protective layer composed of NiCr is provided on each side of the IR reflective layer.
[0052] Known methods, such as sputtering deposition and thermal evaporation, can be used to coat a protective layer on a substrate. When using a NiCr protective layer, the protective layer is preferably sputtered onto a metallic IR reflective layer (e.g., at about 700 W) and deposited from, for example, a DC (direct current) target. When using a ZnO protective layer, the protective layer can be fabricated using plasma containing a stoichiometric excess of oxygen, by plasma deposition utilizing an evaporated zinc source.
[0053] The dielectric layer in a low-emissivity coating performs anti-reflective functions and increases the overall transmittance of the coated article. It also provides protection for the underlying layers. If desired, a low-emissivity coating may include one or more dielectric layers. In some embodiments, two or more consecutive dielectric layers are used.
[0054] There are no particular limitations on the dielectric material used for the dielectric layer. For the purposes of this disclosure, most commonly used dielectric materials can be considered, such as oxides, nitrides, oxynitrides, or combinations thereof. The dielectric material may also be doped with suitable materials, such as Al or stainless steel. When selecting a suitable dielectric material, factors including refractive index n, transparent region, availability of deposition methods, and cost-effectiveness can be considered. Other considerations, such as compatibility with other materials and thermal stability, may also be decisive. Suitable materials for the dielectric layer include TiO2, Ta2O5, Nb2O5, ZrO2, ZnO, ZnS, ZnSe, HfO2, LaTiO3, Al2O3, La2O3, Y2O3, Gd2O3, Sc2O3, Si3N4, and SiAlO. x N y And may include materials selected from SiO2, Al-doped SiO2, LiF, MgF2, Na3AlF6, SnO2, indium tin oxide (ITO), Al-doped zinc oxide (AZO), WO3, SiO x N y One or more of the following. For the purpose of high transmittance and high refractive index, the protective layer preferably comprises TiO2, Nb2O5 and / or Ta2O5 or is composed of TiO2, Nb2O5 and / or Ta2O5. If desired, a SiO2 or Al-doped SiO2 dielectric layer can also be used as an adhesive layer.
[0055] Typically, the thickness of each dielectric layer is adjusted to reduce internal and external reflectivity, thereby achieving high transmittance, for example, >60%. The thickness of each dielectric layer can vary from about 25 nm to about 45 nm. However, it is recommended that the thickness of each dielectric layer on the IR reflective layer be in the range of about 30 nm to about 40 nm.
[0056] The dielectric layers used herein can be deposited using methods known in the art, such as radio frequency magnetron sputtering, DC magnetron sputtering, reactive pulsed magnetron sputtering, thermal evaporation, electron beam evaporation, ion beam sputtering, and atomic layer deposition. The choice of deposition method can depend on the materials to be deposited and the desired optical properties. In some embodiments, when depositing a dielectric layer comprising TiO2 and / or a dielectric layer comprising SiO2, magnetron sputtering (e.g., about 3000 W or 3800 W for TiO2 and about 2000 W for SiO2) is employed, and these layers are prepared by sputtering a Ti or Si target in oxygen.
[0057] In some embodiments, a metallic IR reflective layer is sandwiched between two adjacent protective layers, each protective layer comprising or composed of NiCr and having a thickness of about <5 nm, and the metallic IR reflective layer comprising or composed of Ag and having a thickness of about 20 nm.
[0058] In some embodiments, the coated article disclosed herein includes a low-emissivity coating supported by a substrate, and the low-emissivity coating, from the substrate outwards, sequentially includes: a dielectric layer comprising TiO2 or made of TiO2, a protective layer comprising NiCr or made of NiCr, a metallic IR reflective layer comprising Ag or made of Ag, a protective layer comprising NiCr or made of NiCr, and a dielectric layer comprising TiO2 or made of TiO2. If desired, a dielectric / adhesive layer comprising SiO2 or Al-doped SiO2 or made of SiO2 or Al-doped SiO2 may be added to the dielectric layer comprising TiO2 or made of TiO2 located further outwards on the substrate.
[0059] More specifically, the coated article includes a low-emissivity coating supported by a substrate, and the low-emissivity coating, from the substrate outwards, sequentially includes: a TiO2 dielectric layer of about 25 nm to about 45 nm, a NiCr protective layer of about 5 nm, an Ag metal IR reflective layer of about 10 nm to about 20 nm, a NiCr protective layer of about 5 nm, and a TiO2 dielectric layer of about 25 nm to about 45 nm. In a further embodiment, the coated article includes a low-emissivity coating supported by a substrate, and the low-emissivity coating, from the substrate outwards, sequentially includes: a TiO2 dielectric layer of about 40 nm, a NiCr (80 / 20) protective layer of about 5 nm, an Ag metal IR reflective layer of about 20 nm, a NiCr (80 / 20) protective layer of about 5 nm, and a TiO2 dielectric layer of about 40 nm. In a further embodiment, the coated article includes a low-emissivity coating directly supported by a substrate, and the low-emissivity coating comprises or is composed of the following layers in sequence from the substrate outward: a TiO2 dielectric layer of about 40 nm, a NiCr (80 / 20) protective layer of about 5 nm, an Ag metal IR reflective layer of about 20 nm, a NiCr (80 / 20) protective layer of about 5 nm, a TiO2 dielectric layer of about 40 nm, and a SiO2 or Al-doped SiO2 dielectric / adhesive layer of about 10 nm.
[0060] Frequency-selective surfaces on metallic IR reflective layers are used to enhance the transmission of telecommunication frequencies through the coated article. These frequency-selective surfaces can have periodic patterns, such as periodic triangular grids, periodic square grids, periodic hexagonal grids, periodic circular grids, or periodic mesh grids (see reference). Figure 3 Alternatively, the frequency-selective surface can have a non-periodic pattern, such as a Penrose tessellation. Frequency selectivity can be tuned by varying the geometry and geometric parameters (such as cell size and aperture linewidth) of the periodic pattern to achieve the desired signal transmission at a specific operating frequency. When compared to a coated article with a metallic IR reflective layer but without a frequency-selective surface, the frequency-selective surface used for this purpose can advantageously reduce the attenuation of signal transmission at telecommunication frequencies from about 30 dB to about 1 dB.
[0061] The cell size used in this article refers to the cell size reflecting periodicity, and the aperture linewidth refers to the width of the ablation path. Taking a periodic hexagonal lattice as an example, the cell size is represented by the length of the diagonal (e.g., see reference). Figure 2 For a periodic square grating, the cell size is represented by the diagonal of the square. For a periodic ring grating, the cell size is represented by the diameter. Preferably, the aperture linewidth is small enough that the optical contrast is not visible to the naked eye.
[0062] Frequency-selective surfaces can be fabricated by laser etching. For this purpose, one or more stacks can be laser-etched to create frequency-selective surfaces on a metal layer, and the stacks can be selected from: a substrate / metal layer stack, a substrate / protective layer / metal layer stack, a substrate / dielectric layer / protective layer / metal layer stack, a substrate / dielectric layer / protective layer / metal layer / protective layer stack, a substrate / metal layer / substrate stack, a substrate / protective layer / metal layer / substrate stack, a substrate / dielectric layer / protective layer / metal layer / substrate stack, and a substrate / dielectric layer / protective layer / metal layer / protective layer / substrate stack. For laser etching, the laser beam can enter from either suitable side of the coated article to create the frequency-selective surface on the metal layer. Figure 9 As shown, the laser beam can enter from the substrate side of the coated article or from the side of the coated article opposite to the substrate. This allows for laser etching of fully assembled multilayer glass windows, including metal layers, to create frequency-selective surfaces on the metal layers. Laser scribing can be used in the fabrication if desired. For illustration, a stack of substrate / dielectric layer / protective layer / metal IR reflective layer / protective layer is etched using a pulsed Nd:YAG laser, followed by the growth of one or more layers on the protective layer, such as another dielectric layer and an outermost hard coating. In some embodiments, the stack of substrate / dielectric layer / protective layer / metal IR reflective layer is laser-etched to create a frequency-selective surface. Laser parameters can be optimized to etch only the metal IR reflective layer without reaching the substrate. Alternatively, photolithography can be considered to create the frequency-selective surface. For example, a UV photolithography process can be performed to transfer a pattern from a mask onto a photoresist (photosensitive material), followed by a wet etching process to create the frequency-selective surface. By ablating only a small portion of the IR reflective layer (e.g., 5% to 10% of the layer surface area), the thermal reflective properties and high transmittance of the coated article can be maintained while allowing telecommunication frequencies to pass through.
[0063] In some embodiments, the cell size of the periodic pattern on the frequency-selective surface is less than about 2 mm, for example, less than 1 mm, and the aperture linewidth is from about 5 μm to about 60 μm, for example, from about 30 μm to about 60 μm, for example, 50 μm. It is desirable that the cell size of the periodic pattern on the frequency-selective surface is about 0.5 mm and the aperture linewidth is about 50 μm. In a more preferred embodiment, the periodic pattern on the frequency-selective surface is a periodic hexagonal grid. More preferably, the diagonal of the hexagon is about 0.5 mm, and the aperture linewidth is about 50 μm.
[0064] The inventors have discovered that a hard coating layer can be provided as the outermost layer to protect the underlying layers, thereby improving the durability of the coated article (particularly in terms of abrasion resistance and weather resistance). This, in turn, enables the coated article to be used in automotive, medical, and construction applications. For this purpose, various abrasion-resistant hard coatings based on polysiloxanes are conceivable, and they can typically be applied at a thickness of about 5 μm to about 6 μm. In some embodiments, the polysiloxane-based abrasion-resistant hard coating can be made from a thermosetting liquid polysiloxane nanocomposite hard coating resin containing silica nanoparticles (such as CRYSTALCOAT, commercially available from SDC Technologies). TM MP-101) is prepared. If desired, an adhesive layer can be applied to the low-emissivity coating before applying the hard coating, and the adhesive layer can be made of materials known in the art (e.g., SiO2 or Al-doped SiO2). If a SiO2 or Al-doped SiO2 adhesive layer is used, the thickness of the adhesive layer can be from about 10 nm to about 100 nm, preferably about 10 nm. Dip coating or flow coating can be used to coat the polysiloxane-based hard coating. For dip coating, the substrate receives the coating before thermal curing.
[0065] When no hard coating is available, coated articles, including those with low-emissivity coatings, can be placed inside the cavity of a multi-pane window to isolate them from the atmosphere.
[0066] The coated articles disclosed herein may also contain other layers. In some cases, instead of a hard coating, the coated articles may include, for example, an outer coating made of SiO2 as the outermost layer to improve durability.
[0067] It should be understood that this document also discloses a method for reducing the attenuation of telecommunication frequency signal transmission in a coated article, wherein the coated article includes a metal layer, and the method includes creating a frequency selective surface on the metal layer. The metal layer may be a metallic IR reflective layer within a low-emissivity coating included in the coated article. The coated article and the frequency selective surface can be designed and manufactured with reference to the above discussion.
[0068] In some cases, the coated article according to this disclosure can effectively reflect infrared light or heat while being highly transparent, allowing 5G signals to pass through, making it very useful in windows of public transportation vehicles and buildings. It can also have a simplified design (particularly in some cases, with as few as five to seven coatings). This allows the low-emissivity coating to be applied to at least a portion of the substrate's surface that will be exposed to the environment of use (i.e., facing the atmosphere), eliminating the need to place it between glass panes. Example
[0069] Manufacturing of coated polycarbonate substrates with low-emissivity coating
[0070] Prepare as follows: Figure 1 The coated polycarbonate substrate shown.
[0071] The molded AR polycarbonate (PC) substrate was cleaned with detergent and a non-abrasive sponge, dried with compressed air, and then plasma-cleaned in an Ar atmosphere for 2 minutes.
[0072] TiO2, NiCr, Ag, and Al-doped SiO2 were deposited using a custom-designed in-line magnetron sputtering system. The system employed the following high-purity tubular sputtering targets (80 cm high, 7.5 cm in diameter) that rotated during deposition: Ti (99.99 wt% purity), NiCr (80 wt% Ni, 20 wt% Cr), Si (5 wt% Al doped), and Ag (99.99 wt% purity). The pressure before deposition was 1.5 × 10⁻⁶. -6 mbar, and each target pre-splashed for 4 minutes.
[0073] First, 40 nm of TiO2 was deposited in poison mode using 400 sccm of Ar and 35 sccm of O2, generating a working pressure of 0.00595 mbar. The sputtering power was maintained at 3800 W, and the carrier velocity was 1.04 mm / s.
[0074] Then, NiCr less than 5 nm was deposited at a power of 700 W under a carrier velocity of 39.4 mm / s and a working pressure of 0.00369 mbar (400 sccm of Ar).
[0075] Ag (20 nm) was sputtered onto NiCr at a carrier velocity of 21.4 mm / s and the same working pressure of 0.00369 mbar at a power of 3000 W.
[0076] Again, using the previously defined conditions, NiCr (<5 nm) was grown on patterned Ag, followed by TiO2 (40 nm). This yielded a yield of 5.1 × 10⁻⁶. -3 At a working pressure of mbar, 400 sccm of Ar and 45 sccm of O2 were used to deposit 10 nm of Al-doped SiO2 in poisoned mode at a power of 2000 W. The carrier velocity was 16.4 mm / s.
[0077] Finally, the stack was dip-coated using a Qualtech QPI-168 dip coater with CrystalCoat MP101 (SDC Technologies, 32.5% solids), a transparent hard coating resin composed of siloxane-based materials embedded with silica nanoparticles. A dip rate of 500 mm / min was used to produce a hard coating with a thickness of 5 μm. After dip-coating, the samples were dried for 30 minutes and then cured in an oven at 130°C for 1 hour. The process was carried out at a humidity of 25-45%.
[0078] Figure 8 The resulting low-emissivity coating exhibits a visible light transmittance of approximately 61% and an IR reflectance of approximately 64%. Compared to some commercially available low-emissivity coatings, the low-emissivity coating prepared in this paper not only possesses a simple, low-cost structure but also demonstrates comparable visible light transmittance and comparable IR reflectance. Visible light transmittance and IR reflectance were analyzed using an Agilent Technologies UV-VIS-NIR spectrophotometer (Cary 5000).
[0079] Durability - Abrasion and corrosion of the coated articles prepared above
[0080] Abrasion tests, such as the Bayer and steel wool tests, were performed on the low-emissivity samples. The steel wool test was conducted by Danilee. 2000 TM The friction testing machine is used. In Bayer testing, it is employed... An oscillating abrasion tester (model 6100) was used to evaluate abrasion resistance to fine gravel. In these tests, the higher the abrasion rate, the stronger the abrasion resistance of the sample. Both tests confirmed that the coated product is suitable as a first surface window due to its high abrasion resistance. Figure 4 Almost no visual changes were observed after the experiment.
[0081] The low-emissivity stack was placed in a corrosion chamber for 1000 hours. After 1000 hours (the time required for a commercial vehicle rearview mirror), the appearance of the low-emissivity coating remained almost unchanged, and it produced the same transmittance value. Figure 5a) shows the results of the unprotected stack (without a hard coating) after 24 hours in the corrosion chamber and the results of the protected stack after 1000 hours.
[0082] Fabrication of a coated polycarbonate substrate with a low-emissivity coating, wherein the low-emissivity coating is laser-etched onto a metal IR-reflective layer having a frequency-selective surface.
[0083] The molded AR polycarbonate (PC) substrate was cleaned with detergent and a non-abrasive sponge, dried with compressed air, and then plasma-cleaned in an Ar atmosphere for 2 minutes.
[0084] TiO2, NiCr, Ag, and Al-doped SiO2 were deposited using a custom-designed in-line magnetron sputtering system. The system employed the following high-purity tubular sputtering targets (80 cm high, 7.5 cm in diameter) that rotated during deposition: Ti (99.99 wt% purity), NiCr (80 wt% Ni, 20 wt% Cr), Si (5 wt% Al doped), and Ag (99.99 wt% purity). The pressure before deposition was 1.5 × 10⁻⁶. -6 mbar, and each target pre-splashed for 4 minutes.
[0085] First, 40 nm TiO2 was deposited in poisoned mode using 400 sccm of Ar and 35 sccm of O2, generating a working pressure of 0.00595 mbar. The sputtering power was maintained at 3800 W, and the carrier velocity was 1.04 mm / s.
[0086] Then, NiCr less than 5 nm was deposited at a power of 700 W under a carrier velocity of 39.4 mm / s and a working pressure of 0.00369 mbar (400 sccm of Ar).
[0087] Ag (20 nm) was sputtered onto NiCr at a carrier velocity of 21.4 mm / s and the same working pressure of 0.00369 mbar at a power of 3000 W.
[0088] First, a Frequency Selective Surface (FSS) was designed using AutoCAD. The pattern design was saved as a Graphical Exchange Format (DXF) file and then transferred to a laser ablation apparatus. Periodic hexagonal FSS patterns (0.5 mm cell size) were ablated and evaporated from the Ag film using a Sei Laser Nd:YAG (1064 nm) pulsed laser, G8. The pattern was etched at a frequency of 10 kHz, a speed of 100 mm / s, and a power of 18 W. These parameters produced an ablation linewidth of 50 μm. An extraction system was fixed to the machine to remove fumes generated during the evaporation process.
[0089] Again, using the previously defined conditions, NiCr (<5 nm) was grown on patterned Ag, followed by TiO2 (40 nm).
[0090] The output is 5.1 × 10. -3 At a working pressure of mbar, 400 sccm of Ar and 45 sccm of O2 were used to deposit 10 nm of Al-doped SiO2 in poisoned mode at a power of 2000 W. The carrier velocity was 16.4 mm / s.
[0091] Finally, the stack was dip-coated using a Qualtech QPI-168 dip coater with CrystalCoat MP101 (SDC Technologies, 32.5% solids), a transparent hard coating resin composed of siloxane-based materials embedded with silica nanoparticles. A dip rate of 500 mm / min was used to produce a hard coating with a thickness of 5 μm. After dip-coating, the samples were dried for 30 minutes and then cured in an oven at 130°C for 1 hour. The process was carried out at a humidity of 25-45%.
[0092] The coating on the polycarbonate substrate has the characteristic of a low-emissivity coating with a frequency-selective surface on the metallic IR reflective layer.
[0093] Figure 7 The table below provides the characteristics of coated articles with frequency-selective surfaces and compares them with those of ordinary polycarbonate and coated articles without frequency-selective surfaces.
[0094] FSS technology has also been applied to fully grown low-emissivity coatings. Figure 2 Before growing the top TiO2, Al-doped SiO2, and hard coating, the TiO2 / NiCr / Ag / NiCr film was laser-etched into a hexagonal pattern. The resulting low-emissivity coating showed almost no change in transmittance, and the blocked IR light was reduced by only 10%. Figure 8 ).
[0095] Fabrication of a coated polycarbonate substrate with an Ag film having a frequency-selective surface.
[0096] Using 100mm x 100mm, 4.5mm thick commercial clear hard-coated PC from Bayer ( Abrasion-resistant (AR) film was used as the substrate. The dielectric constant (dielectric constant value) of the PC substrate was 2.96 (Technical Data Sheet, 2023). Before growing the Ag film, the PC substrate was cleaned with soap, rinsed with reverse osmosis (RO) water, and then plasma-treated for 2 minutes to remove any contaminants (Alder et al., 2020). A 10 nm thick Ag film was deposited on the previously cleaned PC substrate using an ion-assisted electron beam evaporation system, Satis Vacuum 725. The substrate was mounted on a rotating stage while being subjected to 1 × 10⁻⁶ ion-assisted electron beam evaporation. -4 The vaporizer was bombarded with Ar ions at a pressure of mbar, and the rotating stage moved at 90 rpm at a height of 750 mm above the vaporizer. Silver particles (99.99% purity) from Kurt J. Lesker were placed in a tungsten crucible and... Evaporation rate. Thickness and deposition rate were monitored in real time using a quartz crystal oscillator (Sycon Instruments, STC-2000A). Although the low-emissivity coating consists of several layers, in this example, only a single silver layer was used to analyze the effect of the pattern, which was responsible for signal attenuation in the low-emissivity coating.
[0097] Some FSS patterns were designed using AutoCAD 2021 and Solidworks 2019 software. The same software program was used to measure the amount (%) of metal area removed from the coating. The pattern designs were saved as Graphic Exchange Format (DXF) files and then transferred to the laser ablation equipment.
[0098] FSS patterns were generated using laser ablation. Periodic patterns were ablated and evaporated from Ag films using Sei Laser's Nd:YAG (1064nm) pulsed laser G8 (G8, 2008). The frequency, power, and speed of the ablation process were optimized to avoid damaging the PC substrate and to obtain the finest possible linewidth; therefore, the patterns were etched at a frequency of 10kHz, a speed of 100mm / s, and a power of 18W. These parameters produced an ablation linewidth of 50±10μm and clean ablation areas. An extraction system was fixed on the machine to remove fumes generated during the evaporation process.
[0099] Various FSS patterns with regular polygonal shapes (e.g., triangles, squares, and hexagons) were laser-etched on a silver-plated PC substrate. The 5G attenuation values (72-82 GHz), optical performance, and morphology of the patterns were analyzed to determine which pattern offered the lowest attenuation without compromising IR reflectivity and visible light transmittance. This was achieved using an automotive radome tester (Rohde & Schwarz). QAR was used to measure signal attenuation (72-82GHz).
[0100] The characteristics of a coated polycarbonate substrate with an Ag coating, wherein the Ag coating has a frequency-selective surface.
[0101] Fabrication of a coated polycarbonate substrate with a low-emissivity coating, wherein the low-emissivity coating has a frequency-selective surface on a metal IR reflective layer via photolithography.
[0102] Figure 10 The following photolithography process is also shown.
[0103] (1) A stack of PC substrate / TiO2 / NiCr / Ag is prepared in the same manner as the coated polycarbonate substrate with low-emissivity coating described above, wherein the low-emissivity coating is laser-etched onto a frequency-selective surface on a metal IR reflective layer.
[0104] (2) Spin-coating a positive photoresist liquid onto the film ( 1518). Then, the sample was cured on a hot plate at 100°C for 1 minute to crosslink the photoresist (soft baking process). The thickness of the photoresist was approximately 1 μm.
[0105] (3) Using a mask alignment system ( 620) UV light (365 nm) was exposed through a mask with a hexagonal patch pattern (D = 0.5 mm, w = 5 μm). The mask (from JD Photo Data) was made of soda-lime glass with a chromium pattern on top, which selectively allowed UV light to pass through, selectively processing the material. The UV light passing through the mask caused chemical changes in the photoresist and altered its structure.
[0106] (4) Coat the surface with developer solution ( 726MIF), and the developer solution dissolves the photoresist areas exposed to UV light, thereby leaving a hexagonal patch pattern on the photoresist layer.
[0107] (5) To transfer the hexagonal pattern onto the Ag layer, a wet etching technique was used, in which the sample was placed in an etching chemical solution (cerium ammonium nitrate (IV)-(NH4)2[Ce(NO3)6]) for 1 minute and 30 seconds. The etching solution penetrated into the hexagonal voids and completely removed the Ag layer.
[0108] (6) After completing the desired pattern, remove any remaining photoresist by rinsing with an acetone solution (CH3COCH3). Immediately after rinsing, spray compressed air to dry the sample and remove any etchant or acetone residue.
[0109] (7) After patterning on the Ag layer, the sample is coated with other layers (NiCr / TiO2 / SiO2 / MP101).
[0110] The resulting low-emissivity coating, supported by the substrate, has a visible light transmittance of approximately 64% and an IR reflectance of approximately 65%. Its 5G attenuation (72-82GHz) is approximately 5.7dB.
[0111] Any reference to prior art in this specification is not, and should not be construed as, an admission or in any way an implication that such prior art constitutes part of common general knowledge.
[0112] It should be understood that the terms “comprise” and “include” as used in this specification and any derivative thereof (e.g., including, including, including, including, including) and the following claims shall be deemed to include the features referred to by the terms and, unless otherwise stated or implied, do not mean that any additional features are excluded.
[0113] In some cases, for brevity and / or to aid in understanding the scope of this disclosure, a single embodiment may combine multiple features. It should be understood that in such cases, these multiple features may be provided individually (in separate embodiments) or in any other suitable combination. Alternatively, where individual features are described in separate embodiments, these individual features may be combined into the single embodiment unless otherwise stated or implied. This also applies to claims that can be recombined in any combination. That is, claims may be modified to include features defined in any other claim. Furthermore, the phrase “at least one” referring to a series of items means any combination of these items, including a single member. As an example, “at least one of a, b, or c” is intended to cover: a; b; c; a and b; a and c; b and c; and a, b, and c.
[0114] Those skilled in the art will understand that the use of this disclosure is not limited to the specific application or the applications described above. This disclosure is also not limited to its preferred embodiments regarding the specific elements and / or features described or shown herein. It should be understood that this disclosure is not limited to the one or more embodiments disclosed, but is capable of various rearrangements, modifications, and substitutions without departing from the scope set forth and defined by the following claims.
Claims
1. A coated article comprising a metal layer, wherein the metal layer has a frequency-selective surface configured to reduce attenuation of telecommunication frequency signal transmission.
2. The coated article according to claim 1, wherein the metal layer is a metal IR reflective layer within a low-emissivity coating included in the coated article.
3. The coated article according to claim 1 or 2, wherein the frequency-selective surface comprises a periodic pattern and / or a non-periodic pattern.
4. The coated article according to claim 3, wherein the periodic pattern is selected from the group consisting of periodic hexagonal grids, periodic square grids, periodic triangular grids, periodic circular grids and periodic lattice grids, and the non-periodic pattern is selected from Penrose tessellation.
5. The coated article according to any one of claims 1 to 4, wherein the frequency-selective surface comprises a periodic pattern having a cell size of less than about 2 mm and a pore linewidth of about 5 μm to about 60 μm, for example about 30 μm to about 60 μm.
6. The coated article according to claim 5, wherein the frequency-selective surface comprises a periodic pattern with a cell size of about 0.5 mm and a pore linewidth of about 50 μm.
7. The coated article of claim 6, wherein the frequency selective surface comprises a periodic hexagonal grid with a cell size of about 0.5 mm and a pore linewidth of about 50 μm.
8. The coated article according to any one of claims 1 to 7, wherein the telecommunication frequency is used for fifth-generation (5G) communication.
9. The coated article according to any one of claims 1 to 8, wherein the attenuation of telecommunication frequency signal transmission is reduced from about 30 dB to about 1 dB when compared with a coated article in which the metal layer has no frequency-selective surface.
10. The coated article according to any one of claims 1 to 9, wherein the metal layer comprises Ag, Al, Cu, Zn, Nb, TiN, Ag / Au alloy, Ag / Cu alloy, Ag / Al alloy, NbN x NbCr, NbCrN x 、NbZrO x And / or Au.
11. The coated article according to any one of claims 1 to 10, wherein the thickness of the metal layer is from about 5 nm to about 25 nm, preferably from about 10 nm to about 20 nm.
12. The coated article according to any one of claims 1 to 11, wherein the coated article comprises a low-emissivity coating supported by a substrate, and the low-emissivity coating comprises, in sequence from the substrate outward, a dielectric layer, a protective layer, a metallic IR reflective layer, a protective layer, and a dielectric layer.
13. The coated article according to any one of claims 1 to 12, wherein the substrate for the coated article is substantially made of plastic or glass.
14. A method for reducing attenuation of telecommunication frequency signal transmission in a coated article according to any one of claims 1 to 13, wherein the method comprises generating a frequency-selective surface on the metal layer.
15. The method of claim 14, wherein a frequency-selective surface is generated on the metal layer by laser etching or photolithography.
16. The method of claim 15, wherein one or more stacks are laser-etched to create a frequency-selective surface on the metal layer, and the one or more stacks are selected from the group consisting of: a substrate / metal layer stack, a substrate / protective layer / metal layer stack, a substrate / dielectric layer / protective layer / metal layer stack, a substrate / dielectric layer / protective layer / metal layer / protective layer stack, a substrate / metal layer / substrate stack, a substrate / protective layer / metal layer / substrate stack, a substrate / dielectric layer / protective layer / metal layer / substrate stack, and a substrate / dielectric layer / protective layer / metal layer / protective layer / substrate stack.
17. The method of claim 16, wherein for the laser etching, the laser beam enters from either side of the stack to create a frequency-selective surface on the metal layer.
18. The method according to any one of claims 15 to 17, wherein the multilayer glass window comprising a metal layer is laser etched to create a frequency-selective surface on the metal layer.
19. The method according to any one of claims 14 to 18, wherein the percentage of the area of the metal layer removed does not exceed about 25% to create a frequency-selective surface on the metal layer.
20. The method according to any one of claims 14 to 19, wherein the percentage of the area of the metal layer removed does not exceed about 20% to create a frequency-selective surface on the metal layer.
21. The method according to any one of claims 14 to 20, wherein the percentage of the area of the metal layer removed does not exceed about 10% to create a frequency-selective surface on the metal layer.
22. Use of the coated article according to any one of claims 1 to 13 or the coated article prepared according to any one of claims 14 to 21 in motor vehicles and buildings.